2013
DOI: 10.2176/nmc.oa2012-0299
|View full text |Cite
|
Sign up to set email alerts
|

The Pitfalls in Surgical Management of Lumbar Canal Stenosis Associated With Rheumatoid Arthritis

Abstract: There have been few clinical studies in the area of cervical spine that focused on surgery for treating degenerative lumbar disease in patients with rheumatoid arthritis (RA). High rates of wound complications and instrumentation failure have been reported more for RA than for non-RA patients, although clinical outcomes are similar between the two groups. Lumbar canal stenosis in RA is caused not only by degeneration but also by RA-related spondylitis, which includes facet arthritis and inflammation around the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Steroid usage has been part of the classic presentation of RA patients and places significant burdens on surgical outcomes in general. Mitsuyama et al also classically reported the pitfalls in surgical management of lumbar spinal canal stenosis in RA patients lie in the higher risk of infection, instrumentation failure and vertebral fracture showing the post-operative results of their 11 out of 12 patients being on steroid [ 24 ]. Second, as treatment options have markedly increased with the introduction of biologics, steroid usage might be interpreted as a surrogate marker of suboptimal RA control [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Steroid usage has been part of the classic presentation of RA patients and places significant burdens on surgical outcomes in general. Mitsuyama et al also classically reported the pitfalls in surgical management of lumbar spinal canal stenosis in RA patients lie in the higher risk of infection, instrumentation failure and vertebral fracture showing the post-operative results of their 11 out of 12 patients being on steroid [ 24 ]. Second, as treatment options have markedly increased with the introduction of biologics, steroid usage might be interpreted as a surrogate marker of suboptimal RA control [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the number of lumbar lesions with RA might increase because the main pathology is degeneration, not synovitis. Thus, life expectancy should increase, resulting in greater age-related degeneration [ 9 ]. The facets and vertebral end-plates are the most important areas affected in the lumbar spine [ 6 , 8 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…The facets and vertebral end-plates are the most important areas affected in the lumbar spine [ 6 , 8 , 10 ]. Consequently, chronic facet arthritis and enthesopathy at the disco-vertebral junction are important findings in the lumbar spine and are present in up to 25% of patients with RA [ 1 , 9 ]. Common pathological findings in the lumbar spine that are encountered in patients with RA are degenerative spondylolisthesis, endplate erosions, disc space narrowing, facet erosion, facet cysts, and vertebral fractures secondary to osteoporosis [ 2 , 11 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Compared to patients without RA, patients with RA who undergo surgical management have worse subjective scoring outcomes and increased rates of complications. 21 , 48 Common complications include wound infections, pseudoarthrosis, nonunion, implant complications, and adjacent level degeneration. A recent outcomes study of posterolateral lumbar fusion showed that compared to patients without RA, those with RA had almost a 3-fold increase in complications such as radiographic evidence of nonunion ( P = .001), implant failure ( P = .032), symptomatic adjacent segment disease ( P = .001), and infection ( P = .031).…”
Section: Complicationsmentioning
confidence: 99%
“… 19 Furthermore, patients with RA have higher frequencies of vertebral fractures and higher complication rates following surgical interventions compared to patients without RA undergoing similar interventions. 20 , 21 The management of RA affecting the cervical spine is well described, but there are limited studies discussing the management of rheumatoid involvement of the lumbar spine.…”
Section: Introductionmentioning
confidence: 99%